How to Measure Everything : A fun first guide to the maths of measuring - McArdle, Sean; Lattin, Molly (London : Dorling Kindersley Limited, 2018)
Lift the flaps, spin the wheels, and let's get measuring! Every page is packed with top tips for all types of measuring, from heights and weights to temperature and telling the time. Fun comparisons, quizzes, and a fabulous pop-up scene help kids get to grips with measuring things in the world around them.
Ages 5+.
Keywords: Measurement -- Juvenile literature; Board books; Lift-the-flap books; Toy and movable books